The Influence of Human Development Index, Population Number, and Economic Growth on Poverty in Bengkulu Province, 2013-2022 - Aniska Julia Putri; Novi Tri Putri (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
The purpose of this study is to analyse the relationship between the Human Development Index (HDI), population, and growth rate in Bengkulu province districts and cities over the period of 2013-2022. This study employs quantitative approaches to data collection. Bengkulu province was represented in this study with a sample that includes ten of its districts and cities. Secondary data collected by the British Statistics Service (BPS) were used for this study's research. A panel data regression model served as the basis for the study methodology used to analyse the collected data. In light of this investigation, FEM was determined to be the most suitable model. The ratio of 95% implies that the independent variables HDI, population, and economic growth have the potential to explain poverty factors in districts and cities in Bengkulu province with a ratio of 95% while the remaining 5% is explained by other variables. The r-squared value is 0.959038, which translates to 95%. excluded from the scope of this study model. According to the findings of the study, the HDI coefficient is -0.225, the probability value is 0.0740, which indicates that it has neither a positive nor a significant influence on poverty, and the population coefficient value is -6.730, with a probability value of 0.0001. economic growth has a coefficient of 0.045 with a probability value of 0.05175, suggesting it has no significant impact on poverty in the districts or cities of Bengkulu province in 2013-2022. this indicates that it has a negative and significant affect.